Guibourtacacidin: a new Leuco-anthocyanidin from Rhodesian copalwood; (Guibourtia coleosperma) - De Bruyn, Guustaaf Cornelis (Rhodes University, Faculty of Science, Department of Chemistry, 1962)
A new leuco-anthocyanidin, (+)-7,4'dihydroxyflavan- 3:4-diol has been isolated from the heartwood of Guibourtia coleosperma. The heartwood extractives were fractionated by enrichment procedures involving fractional precipitation and Craig partitioning, to give a high RF (subscript) low molecular weight fraction containing the above leuco -anthocyanidin. This was further fractionated by "preparative" paper chromatography . The leuco-anthocyanidin was amorphous and present in low proportion (0.004%) in the wood. On boiling with alcoholic hydrochloric acid the compound gave an anthocyanidin which was identified as 3,7,4'-trihydroxyflavylium chloride. The degradation products formed by alkali fusion, on a micro-scale, were resorcinol and â™-resorcylic acid, and also p (underscore)-hydroxybenzoic acid. This indicated resorcinol and phenol A and B nuclei respectively. The formation of amorphous dimethyl ether and tetra-acetoxy derivatives indicated two phenolic and two alcoholic hydroxyl groups. The above indicates that the compound was 7,4'-dihydroxyflavan- 3:4- diol and a molecular weight estimation showed it to be monomeric. Comparison of the infrared absorption spectra of the natural dimethyl ether with synthetic (Â±) dimethoxyflavan- 3:4-diol, to which a tentative 2:3- trans- 3:4-cis conformation had been assigned (Phatak and Kulkarni 94), showed close identity. Crystalline (Â±)-7, 4 '-dihydroxyflavan- 3:4 - diol was synthesised by catalytic hydrogenation over platinum oxide of the corresponoing (Â±) -7,4'-dihydroxyflavanonol. The flavanonol was synthesised by sodium hyposulphite reduction of the 7,4 ' -dihydroxyflavonol. The infrared absorption spectra of the natural and synthetic diols were similar but not identical. Chromatographic evidence showed the apparent identity of the synthetic and natural flavan- 3:4- diols, and two possible configurations were assigned for the natural flavan-3:4-diol. The new leuco-anthocyanidin was observed to form an O(underscore)-ethyl ether derivative on manipulation in ethanol. A monomeric leuco- fisetinidin from the heartwood was identified, by two dimensional paper chromatography, as (+) - mollisacacidin. The condensed tannins found also in the heartwood of G.(underscore)- coleosperma appear to be polymeric forms of leuco - fisetinidin and leuco - guibourtinidin. These polymeric tannins form a large proportion of the heartwood extractives and furnish high yields of fisetinidin and guibourtinidin chlorides on boiling with alcoholic hydrochloric acid. Examination of some other members of the Guibourtia spp . by paper chromatography showed that only G (underscore). coleosperma contained the new leuco - anthocyanidin as well as a leuco - fisetinidin. G. (underscore) tessmannii and G. (underscore) demeusii heartwoods contained only leuco-fisetinidin and the related polymers and a close chemical relationship to G.(underscore) coleosperma is thus apparent. G.(underscore) arnoldiana on the other hand is not chemically interrelated with the above members since it appeared to contain only leuco - cyanidin. (Â±) - 7,4 ' -Dihydroxyflavan- 4-ol was synthesised by hydrogenation of the corresponding flavanone over platinum oxide. Observations were made regarding its reddenig and ease of condensation.
Keywords: Phanerogams; Angiosperms; Flavonoids; Anthocyanidins